2012
DOI: 10.3174/ajnr.a2858
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy of 500 Small Asymptomatic Unruptured Intracranial Aneurysms

Abstract: BACKGROUND AND PURPOSE:Although the natural course of UIAs remains unclear, the risk of aneurysmal SAH due to small (Ͻ10 mm) asymptomatic UIAs is low. Endovascular therapy for UIAs has increased because of device development and the need for less invasive treatment. We report the results, safety, and efficacy of endovascular therapy of small asymptomatic UIAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 21 publications
3
50
0
Order By: Relevance
“…Of these, 2690 aneurysms (57.7%) were completely occluded and 1490 (31.9%) had small residual necks. The rate of incomplete occlusion following coiling ranged from 1.2% to 20.8% in larger studies, [17][18][19][20][21][22][23] similar to our finding of 8% in the coiling group. The rate of complete occlusion in the FD group with at least 6 months of follow-up of 64.4% is lower than that in other flow-diverter studies; however, the low rate of retreatment (6%) is in line with those previously reported.…”
Section: Angiographic Outcomessupporting
confidence: 78%
“…Of these, 2690 aneurysms (57.7%) were completely occluded and 1490 (31.9%) had small residual necks. The rate of incomplete occlusion following coiling ranged from 1.2% to 20.8% in larger studies, [17][18][19][20][21][22][23] similar to our finding of 8% in the coiling group. The rate of complete occlusion in the FD group with at least 6 months of follow-up of 64.4% is lower than that in other flow-diverter studies; however, the low rate of retreatment (6%) is in line with those previously reported.…”
Section: Angiographic Outcomessupporting
confidence: 78%
“…Although Im et al 9 and Oishi et al 10 have recently reported comparatively large-volume series, most …”
Section: Discussionmentioning
confidence: 99%
“…However, the patients were a mean of 10 years, and most aneurysms (87.3%) were <10 mm. Although the Japanese guidelines recommend treating UIAs ≥5 mm in maximal diameter, 15 UIAs <5 mm account for 35.4% of the total; Oishi et al 10 reported that 223 (44.6%) of 500 small (<10 mm in diameter) treated UIAs were <5 mm. As part of the annual health checks characteristic of the unique Japanese healthcare system, complete physical examinations and whole brain screenings are widespread, and more small UIAs have been discovered through these routine procedures than elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations